Optimal reliable strategy of virtual power plant in energy and frequency control markets - Soltani, M.; Raoofat, M.; Rostami, M. A. (2012 Proceedings of 17th Conference on Electrical Power Distribution Networks, 2012)
Virtual Power Plant (VPP) is a new entity in power systems which possesses or manages a group of DGs, Energy Storage devices and curtailable loads. This paper presents a novel approach for optimum operation of a VPP in both energy and secondary frequency control (SFC) markets; considering reliability worth of DGs. DGs in the VPP can operate both in peak shaving or standby mode. Operating the DG in peak shaving mode will reduce the VPP's cost while standby operation of the DG may reduce the customers' interruption cost. The reliability worth and the energy cost evaluations are needed to determine whether DG should be operated in peak shaving mode or as standby power. By applying the Monte Carlo simulation method the effect of reliability worth is taken into account precisely. A combined cost function is proposed and solved using linear programming method. The proposed approach in this paper determines the optimum hourly operating strategy of the DG. It creates a single operating profile from a composite of the parameters characterizing each distributed energy resource (DER) in the VPP. Based on this decision, the VPP bids to the market.